Artifical Intelligence as Disruption Factor in the Civil Law: Impact of the use of Artifical Intelligence in Liability, Contracting, Competition Law and Consumer Protection with Particular Reference to the German and Indonesian Legal Situation - Stefan Koos (Yuridika, 2021)
The Article describes the impact of artificial intelligence in different areas of the civil law, namely tort law, contract law, antitrust law and consumer protection law. It shows that the use of artificial intelligence already leads to legal constellations, which cannot longer easily subsumized under elementary terms of the civil law and therefore cause a real disruption in the civil law. Terms, which are based on a freedom concept of the subjective rights of the actors, such as private autonomy and contractual will not fit anymore to the activity of artificial intelligence systems the more those systems are able to act independant of human actors. Similar applies to terms which are referring to the freedom of decision like the market behaviour in the competition law. The article discusses several solution approaches, such as personification approches, agent-principal approaches and the definition of new categories of market and contractual acting. In the consumer protection the special focus in the future legal development will be on the problem how to achieve adequate, though not overflowing, transparency for consumers, especially regarding the combination of big data and algorithms.